ANALISIS KELAYAKAN FINANSIAL PADA USAHA PETERNAKAN AYAM BROILER PT MALINDO DI DESA JAKE KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Aldo Ciptawan Pebrianda; Khairizal; Azharuddin M. Amin; Ilma Satriana Dewi; Khairudin (UIR Press, 2024)
Livestock farming, particularly broiler chicken farming, is a well-known venture in the community. This type of farming incorporates selective and advanced technological inputs to enhance the production and productivity of chicken farmers in a professional manner. The objective of this study is to evaluate the financial viability of broiler chicken farming in Jake Village, located in the Kuantan Tengah District of Kuantan Singingi Regency, Riau Province. Using a case study approach, the research involved direct interviews with farmers. The study was conducted over six months, from October 2023 to March 2024, with respondents including business owners and workers. Data was analyzed using both qualitative and quantitative descriptive methods, incorporating both primary and secondary data sources. The findings from the financial feasibility analysis indicate that the business is viable for operation and growth, having met the investment criteria with a Net Present Value (NPV) of 443,513,051 (greater than 0), an Internal Rate of Return (IRR) of 35% (exceeding the prevailing interest rate of 14% used in this study), a Net Benefit-Cost Ratio (Net B/C) of 1.76 (greater than 1), and a payback period of 3 years and 21 days projected over the next decade.